Distribution frequency of FCER2 genotypes related to corticosteroid response in asthma children treated at National Hospital of Pediatrics - Duong, Thi Ly Huong (Association Franco-Vietnamienne de Pneumologie, 2016)
Recent studies showed that FCER2 is an important gene related to regulate IgE production which is a mediator associated with asthma. Method. In this study, PCR-Sequencing was used to analyze FCER2 polymorphism in 130 patients at National Hospital of Paediatrics. Results. The results of the present study showed that 17 SNPs in FCER2 were identified and had strong linkage. These 17 SNPs recombinated into 5 haplotypes, in which h1 and h2 had the most frequency; Rs28364072 polymorphism in FCER2 is well known to be associated with exacerbation of asthma, subjects who were homozygous for the CC mutant alleles was significantly associated with elevated IgE level, severe exacerbations, the risk of asthma-related hospitalization, and also associated with increased daily corticosteroid dose. Conclusion. In this study, frequency of alleles C in rs28364072 in asthmatic children was similar with that in Kinh HoChiMinh city in the project genome 3, but significantly different from patient group without asthma (p<0,05).